Cement composite material containing steel slag waste and preparation method thereof
By adding modified steel slag, fly ash, ore powder and modified polypropylene fibers to cement composites, the problems of insufficient crack resistance and durability of traditional cement composites are solved, and the material performance is significantly improved and industrial waste is efficiently reused.
Patent Information
- Application Number
- CN202510069788.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-25
AI Technical Summary
Traditional cement composite materials have shortcomings in crack resistance and durability, and the emission of industrial solid waste has put pressure on the environment. How to use industrial solid waste to improve the performance of cement composites has become a hot topic of research.
By adding modified steel slag, fly ash, ore powder and modified polypropylene fibers, the strength and durability of cement composite materials are significantly enhanced, and the reuse of industrial waste is realized, reducing environmental pollution and production costs.
It significantly improves the compressive, flexural, impact and permeability of cement composite materials, extends its service life, and achieves efficient reuse of industrial waste, reducing environmental pollution and production costs.
Smart Images

Figure BDA0005245371570000021 
Figure BDA0005245371570000031 
Figure BDA0005245371570000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cement composite materials, and particularly relates to a cement composite material containing steel slag waste and a preparation method thereof. Background Art
[0002] With the rapid development of infrastructure construction, cement composites have been widely used in roads, bridges, buildings and other fields. However, traditional cement composites have some problems during use, such as poor crack resistance and insufficient durability, which affect the safety and service life of engineering structures. At the same time, the large-scale discharge of industrial solid waste has also brought great pressure to the environment. Therefore, how to use industrial solid waste to improve the performance of cement composites has become a research hotspot.
[0003] The patent with application number CN201410810060.X provides a steel slag aggregate lightweight fiber foam concrete, whose raw materials include 42.5 cement, steel slag aggregate, admixture, additive, polypropylene fiber, etc. The concrete products provided by the invention are light in weight, good in thermal insulation performance, high in toughness, and can effectively utilize existing industrial waste resources to improve resource utilization. Steel slag is a by-product in the steel production process with huge output, but because it contains free calcium oxide (f-CaO) and other components, it has low hydration activity and poor volume stability, and its application in road materials is limited. The f-CaO in the steel slag is unevenly distributed and locally enriched. When it encounters water, it will undergo a hydration reaction, resulting in volume expansion and destroying the material structure. In addition, the steel slag has a large particle size, and the skeleton structure formed is easily damaged during local expansion, affecting the overall performance. Polypropylene fiber is often used to strengthen and toughen cement-based materials, but it has many disadvantages. It has poor adhesion to the cement matrix and mainly relies on physical adsorption and mechanical anchoring. The fibers are easily pulled out under external forces, reducing the strengthening and toughening effect. The high alkaline environment produced by cement hydration will degrade the molecular chain of polypropylene fibers, resulting in a decrease in mechanical properties and affecting long-term stability. Polypropylene fibers have a low melting point and will melt under high temperature or fire conditions, losing their reinforcing effect and forming defects in the matrix.
[0004] In order to solve these problems, relevant research is constantly being carried out. In terms of steel slag utilization, a variety of regulatory approaches are adopted, such as introducing active components, adding industrial solid waste, introducing lightweight components, etc., to carry out material design and performance research, while focusing on key parameter design, including road performance research, etc., but there are still key technical problems to be broken through. In terms of polypropylene fiber modification, its adhesion to the cement matrix is improved by grafting copolymerization and other methods, and alkali-resistant groups are introduced to copolymerize to improve alkali resistance, etc., but the existing technology still needs to be further optimized to better realize the synergistic application of steel slag and polypropylene fiber in cement compositions, improve the comprehensive performance of cement-based materials, and reduce production costs at the same time, realize the resource utilization of industrial solid waste, and promote sustainable development. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a cement composite material containing steel slag waste and a preparation method thereof. The cement composite material significantly enhances the strength and durability of the material by adding modified steel slag, fly ash, mineral powder and modified polypropylene fiber, while achieving effective recycling of industrial waste and reducing environmental pollution and production costs.
[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:
[0007] A cement composite material containing steel slag waste, comprising the following components in parts by weight: 80-100 parts of cement, 20-40 parts of modified steel slag, 20-30 parts of fly ash, 20-30 parts of mineral powder, and 10-20 parts of modified polypropylene fiber;
[0008] The preparation method of the modified polypropylene fiber is as follows:
[0009] S1. Mix 4-(2-aminoethyl)pyridine and 3-(3-(bromomethyl)phenyl)propionic acid evenly, raise the temperature to 50-60° C., stir for 30-50 min, then add tetrabutylammonium bromide, raise the temperature to 90-100° C., reflux for 5-7 h under stirring, cool to room temperature, and purify to obtain an intermediate;
[0010] S2. The intermediate obtained in step S1 and 4-hydroxycrotonic acid are uniformly mixed under stirring conditions, the temperature is raised to 60-70° C., concentrated sulfuric acid is then added dropwise over 40-60 min, the temperature is then raised to 80-90° C., the reaction is refluxed for 4-6 h, the mixture is cooled to room temperature, and a modifier is obtained after purification;
[0011] S3, dispersing polypropylene fiber and benzoyl peroxide in xylene under stirring and nitrogen atmosphere, raising the temperature to 45-55° C., reacting for 45-55 min, then raising the temperature to 70-90° C., continuing the reaction for 20-40 min, removing the solvent, adding the modifier obtained in step S2, reacting at 80-90° C. for 60-80 min, cooling to room temperature, and obtaining modified polypropylene fiber after purification;
[0012] Among them, the synthetic route of the modifier is as follows:
[0013]
[0014]
[0015] The invention uses 4-(2-aminoethyl)pyridine and 3-(3-(bromomethyl)phenyl)propionic acid as starting materials, and carries out N-alkylation reaction under the catalytic action of tetrabutylammonium bromide to obtain an intermediate; then uses the intermediate and 4-hydroxycrotonic acid as raw materials, and carries out esterification reaction under the catalytic action of concentrated sulfuric acid to obtain a modifier; finally, under the action of benzoyl peroxide, the modifier is used to modify polypropylene fiber to obtain modified polypropylene fiber.
[0016] In order to functionally modify the polypropylene fiber, the molar ratio of 4-(2-aminoethyl)pyridine, 3-(3-(bromomethyl)phenyl)propionic acid and tetrabutylammonium bromide in step S1 is 1.6:1.3-1.5:0.03-0.05; the mass ratio of the intermediate, 4-hydroxycrotonic acid and concentrated sulfuric acid in step S2 is 1:1.8-2.2:0.02-0.03; the mass ratio of the polypropylene fiber, benzoyl peroxide and modifier in step S3 is 100:3-5:14-18, and the amount of benzoyl peroxide added to the xylene is 8-12 g / L.
[0017] Furthermore, the preparation method of the modified steel slag is: dispersing the steel slag in an acetic acid aqueous solution, introducing carbon dioxide gas, controlling the partial pressure of carbon dioxide to 0.4 MPa, activating at a temperature of 170-190° C. for 3-5 hours, cooling to room temperature, separating the solid and the liquid, taking the solid, drying and grinding to obtain the modified steel slag; wherein the solid-liquid ratio of the steel slag to the acetic acid aqueous solution is 0.3-0.5 g / mL, the mass fraction of acetic acid in the acetic acid aqueous solution is 2-5%, and the particle size of the modified steel slag is less than 0.075 mm.
[0018] The present invention also provides a method for preparing a cement composite material containing steel slag waste, comprising the following steps: uniformly mixing cement, modified steel slag, fly ash, mineral powder and modified polypropylene fiber to obtain the composite material.
[0019] The present invention has the following beneficial effects:
[0020] The present invention sequentially prepares modified polypropylene fiber through N-alkylation reaction, esterification reaction, and free radical grafting reaction, and introduces carboxyl, benzene ring and pyridine ring into the polypropylene fiber structure. Carboxyl can react with calcium ions generated by cement hydration to form a complex reaction, thereby enhancing the chemical bonding force between the fiber and the cement matrix, so that the modified polypropylene fiber forms a more stable three-dimensional network structure in the cement matrix, and when the cement composition is impacted, the fiber can absorb and disperse energy to prevent the expansion of cracks, thereby improving the toughness and impact resistance of the cement composition. In a high temperature environment or when cement products experience fire and other situations, polypropylene fiber is prone to melting, and cement components containing polypropylene fiber will crack and peel off due to fiber melting, and can no longer effectively play a bearing and protective role. The introduction of benzene ring can improve the heat resistance of fiber, and the conjugated structure of benzene ring has high stability, which can resist molecular chain breakage and degradation at high temperature. In a high temperature environment, the fiber can maintain the integrity of its structure, thereby continuing to play a reinforcing role in the cement composition. The nitrogen atom on the pyridine ring has a lone pair of electrons, which can interact with the cations in the alkali in an alkaline environment to form a relatively stable structure. In the high-alkali environment generated by cement hydration, this structure can reduce the attack of the alkali on the main chain of the polypropylene fiber and improve the alkali resistance of the fiber, thereby maintaining the reinforcing effect of the fiber in the cement matrix and extending the service life of cement products. In addition, the pyridine ring has a certain polarity, and cement is an inorganic material with multiple ionic components. The pyridine group can interact with metal ions such as calcium ions in the cement matrix, such as coordination bonding. This interaction enables the fiber to be better anchored in the cement matrix. When the cement composition is subjected to external force, this good bonding can more effectively transfer stress and further improve the impact resistance of cement products.
[0021] The modified steel slag is compounded with modified polypropylene fiber. The modified steel slag after activation can participate in the hydration reaction of cement to generate more hydration products, which are filled in the pores of the cement matrix to improve the density of the cement matrix. The polypropylene fiber plays a role of binding and crack prevention in the cement matrix, reduces the generation and development of cracks, and enables the cement matrix to bear a larger load, thereby significantly improving the compressive and flexural strengths of the cement composition. The polypropylene fiber can reduce the number, length and width of cracks in the cement composition, and reduce the possibility of generating through cracks. At the same time, the three-dimensional network structure formed by the polypropylene fiber in the cement matrix also plays an effect of blocking the capillary action in the concrete, preventing The penetration of moisture, the interaction between the active ingredients in the modified steel slag and the cement hydration products optimizes the microstructure of the cement matrix, makes the cement matrix more compact, further improves the impermeability of the cement composition, reduces the intrusion of external moisture, etc., thereby improving the anti-permeability and durability of the cement composition; the cement composition is prone to shrinkage cracks during the hardening process, and the addition of polypropylene fiber can effectively reduce the shrinkage cracks of concrete. The filling and active effect of the modified steel slag can optimize the structure of the cement matrix and reduce the shrinkage caused by cement hydration. The combined effect of the two further reduces the occurrence of shrinkage cracks in the cement composition and improves the volume stability of the cement composition. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0023] Polypropylene fiber, length 12-16 mm, density 0.91 g cm -3 , tensile strength ≥500MPa; steel slag, derived from steel slag waste, particle size less than 4.75mm, main components are CaO 32.0wt.%, SiO2 19.1wt.%, Fe2O3 22.0wt.%, Al2O3 6.3wt.%, MgO 3.9wt.%; ore powder is S95 grade ore powder, fineness is 500 mesh, density is 2.80g / cm 3 , content 99%, purchased from Handan Iron and Steel Company of Hebei Iron and Steel Group; cement is P·I42.5 silicate cement, cement density is 3.10g / cm 3 , purchased from China United Cement Group Co., Ltd.; fly ash is first-grade fly ash, density 2.45g / cm 3 , compressive strength 7MPa, particle size 800 mesh, brand Shengtong. The raw materials used in the following examples are all common commercial products.
[0024] Example 1
[0025] A cement composite material containing steel slag waste, comprising the following components in parts by weight: 90 parts of cement, 30 parts of modified steel slag, 25 parts of fly ash, 25 parts of mineral powder, and 15 parts of modified polypropylene fiber;
[0026] The preparation method of the modified steel slag is as follows: dispersing the steel slag in an acetic acid aqueous solution with a mass fraction of 3%, introducing carbon dioxide gas (gas purity is 98%), controlling the partial pressure of carbon dioxide to be 0.4 MPa, activating at a temperature of 180° C. for 4 hours, cooling to room temperature, separating the solid from the liquid, taking the solid, drying it, and grinding it into particles with a particle size of less than 0.075 mm to obtain the modified steel slag; wherein the solid-liquid ratio of the steel slag to the acetic acid aqueous solution is 0.4 g / mL;
[0027] The preparation method of the modified polypropylene fiber is:
[0028] S1. After 4-(2-aminoethyl)pyridine and 3-(3-(bromomethyl)phenyl)propionic acid are mixed uniformly, the temperature is increased to 55°C, stirred for 40 minutes, and then tetrabutylammonium bromide is added, and the temperature is increased to 95°C. Under stirring conditions, the mixture is refluxed for 6 hours, and naturally cooled to room temperature. Toluene is added to the reaction mixture for extraction, and the mixture is shaken and mixed uniformly. The mixture is allowed to stand for 30 minutes, and the organic phase is obtained by separation. A 10wt% sodium hydroxide aqueous solution is added to the organic phase, and the mixture is shaken and mixed uniformly. The organic phase is taken after standing for stratification, and then washed with deionized water, vacuum dried, and distilled under reduced pressure to obtain an intermediate; wherein the molar ratio of 4-(2-aminoethyl)pyridine, 3-(3-(bromomethyl)phenyl)propionic acid, and tetrabutylammonium bromide is 1.6:1.4:0.04, the volume ratio of toluene, 10wt% sodium hydroxide aqueous solution, and deionized water is 100:50:60, and the mass volume ratio of 4-(2-aminoethyl)pyridine to toluene is 0.3g / mL;
[0029] S2, under stirring conditions, the intermediate obtained in step S1 and 4-hydroxycrotonic acid are mixed uniformly, the temperature is increased to 65°C, and then 98% concentrated sulfuric acid is added dropwise, and the addition is completed in 50 minutes, and then the temperature is increased to 85°C, reflux reaction is carried out for 5 hours, and naturally cooled to room temperature, saturated sodium carbonate solution is added to the reaction mixture, shake and mix uniformly, stand and separate for 20 minutes, separate the liquid to obtain an organic phase, and then add saturated brine to the organic phase, shake and wash, and then vacuum dry and distill under reduced pressure to obtain a modifier; wherein the mass ratio of the intermediate, 4-hydroxycrotonic acid, and concentrated sulfuric acid is 1:2:0.025, and the volume ratio of concentrated sulfuric acid, saturated sodium carbonate solution, and saturated brine is 1:15:10;
[0030] The NMR results of the modifier are: 1H NMR (300MHz, DMSO-d6) δ12.05 (s, 1H), 8.55 (d, 2H), 7.58 (t, 1H), 7.18-7.23 (m, 6H), 6.2 3(d, 1H), 4.69(d, 2H), 4.16(s, 1H), 3.76(s, 2H), 3.47(t, 2H), 2.85(t, 4H), 2.53(t, 2H);
[0031] S3. Dispersing polypropylene fiber and benzoyl peroxide in xylene under stirring and nitrogen atmosphere, raising the temperature to 50° C., reacting for 50 min, then raising the temperature to 80° C., continuing the reaction for 30 min, removing xylene, adding the modifier obtained in step S2, reacting at 85° C. for 70 min, naturally cooling to room temperature, washing the reaction product with water and then with acetone, then extracting with acetone for 12 h, and vacuum drying to obtain modified polypropylene fiber; wherein the mass ratio of polypropylene fiber, benzoyl peroxide, and modifier is 100:4:16, and the amount of benzoyl peroxide added to xylene is 10 g / L; the grafting rate of the modified polypropylene fiber is determined by acid-base titration, and the grafting rate is 8.3%.
[0032] A method for preparing a cement composite material containing steel slag waste comprises the following steps: cement, modified steel slag, fly ash, mineral powder and modified polypropylene fiber are uniformly mixed to obtain the composite material.
[0033] Example 2
[0034] A cement composite material containing steel slag waste, comprising the following components in parts by weight: 100 parts of cement, 20 parts of modified steel slag, 30 parts of fly ash, 30 parts of mineral powder, and 20 parts of modified polypropylene fiber;
[0035] The preparation method of the modified steel slag is as follows: dispersing the steel slag in an acetic acid aqueous solution with a mass fraction of 4%, introducing carbon dioxide gas (gas purity is 98%), controlling the partial pressure of carbon dioxide to be 0.4 MPa, activating at a temperature of 190° C. for 3 hours, cooling to room temperature, separating the solid from the liquid, taking the solid, drying it, and grinding it into particles with a particle size of less than 0.075 mm to obtain the modified steel slag; wherein the solid-liquid ratio of the steel slag to the acetic acid aqueous solution is 0.3 g / mL;
[0036] The preparation method of the modified polypropylene fiber is:
[0037] S1. After 4-(2-aminoethyl)pyridine and 3-(3-(bromomethyl)phenyl)propionic acid are mixed uniformly, the temperature is raised to 60°C, stirred for 30 minutes, and then tetrabutylammonium bromide is added, and the temperature is raised to 100°C. Under stirring, the mixture is refluxed for 5 hours, and naturally cooled to room temperature. Toluene is added to the reaction mixture for extraction, and the mixture is shaken and mixed uniformly. The mixture is allowed to stand for 30 minutes, and the organic phase is separated to obtain an organic phase. A 10wt% sodium hydroxide aqueous solution is added to the organic phase, and the mixture is shaken and mixed uniformly. The organic phase is taken after standing for stratification, and then washed with deionized water, vacuum dried, and distilled under reduced pressure to obtain an intermediate; wherein the molar ratio of 4-(2-aminoethyl)pyridine, 3-(3-(bromomethyl)phenyl)propionic acid, and tetrabutylammonium bromide is 1.6:1.3:0.03, the volume ratio of toluene, 10wt% sodium hydroxide aqueous solution, and deionized water is 100:50:60, and the mass volume ratio of 4-(2-aminoethyl)pyridine to toluene is 0.3g / mL;
[0038] S2. Mix the intermediate obtained in step S1 and 4-hydroxycrotonic acid under stirring, raise the temperature to 70°C, then add 98% concentrated sulfuric acid dropwise, complete the addition in 40 minutes, raise the temperature to 90°C, reflux for 4 hours, cool naturally to room temperature, add saturated sodium carbonate solution to the reaction mixture, shake and mix evenly, let stand for 20 minutes, separate the liquid to obtain an organic phase, add saturated brine to the organic phase, shake and wash, then vacuum dry and distill under reduced pressure to obtain a modifier; wherein the mass ratio of the intermediate, 4-hydroxycrotonic acid and concentrated sulfuric acid is 1:1.8:0.02, and the volume ratio of concentrated sulfuric acid, saturated sodium carbonate solution and saturated brine is 1:15:10;
[0039] S3. Dispersing polypropylene fiber and benzoyl peroxide in xylene under stirring and nitrogen atmosphere, raising the temperature to 55° C., reacting for 45 min, then raising the temperature to 90° C., continuing the reaction for 20 min, removing xylene, adding the modifier obtained in step S2, reacting at 90° C. for 60 min, naturally cooling to room temperature, washing the reaction product with water and then with acetone, then extracting with acetone for 12 h, and vacuum drying to obtain modified polypropylene fiber; wherein the mass ratio of polypropylene fiber, benzoyl peroxide, and modifier is 100:3:14, and the amount of benzoyl peroxide added to xylene is 8 g / L; the grafting rate of the modified polypropylene fiber is determined by acid-base titration, and the grafting rate is 8.5%.
[0040] Example 3
[0041] A cement composite material containing steel slag waste, comprising the following components in parts by weight: 80 parts of cement, 40 parts of modified steel slag, 20 parts of fly ash, 20 parts of mineral powder, and 10 parts of modified polypropylene fiber;
[0042] The preparation method of the modified steel slag is as follows: dispersing the steel slag in an acetic acid aqueous solution with a mass fraction of 2%, introducing carbon dioxide gas (gas purity is 98%), controlling the partial pressure of carbon dioxide to be 0.4 MPa, activating at a temperature of 170° C. for 5 hours, cooling to room temperature, separating the solid from the liquid, taking the solid, drying it, and grinding it into particles with a particle size of less than 0.075 mm to obtain the modified steel slag; wherein the solid-liquid ratio of the steel slag to the acetic acid aqueous solution is 0.5 g / mL;
[0043] The preparation method of the modified polypropylene fiber is:
[0044] S1. After 4-(2-aminoethyl)pyridine and 3-(3-(bromomethyl)phenyl)propionic acid are mixed uniformly, the temperature is increased to 50°C, stirred for 50 min, and then tetrabutylammonium bromide is added, and the temperature is increased to 90°C, refluxed for 7 h under stirring, and naturally cooled to room temperature. Toluene is added to the reaction mixture for extraction, and the mixture is shaken and mixed uniformly. The mixture is allowed to stand for 30 min, and the organic phase is obtained by separation. A 10wt% aqueous sodium hydroxide solution is added to the organic phase, and the mixture is shaken and mixed uniformly. The organic phase is taken after standing for stratification, and then washed with deionized water, vacuum dried, and distilled under reduced pressure to obtain an intermediate; wherein the molar ratio of 4-(2-aminoethyl)pyridine, 3-(3-(bromomethyl)phenyl)propionic acid, and tetrabutylammonium bromide is 1.6:1.5:0.05, the volume ratio of toluene, 10wt% aqueous sodium hydroxide solution, and deionized water is 100:50:60, and the mass volume ratio of 4-(2-aminoethyl)pyridine to toluene is 0.3 g / mL;
[0045] S2. Mix the intermediate obtained in step S1 and 4-hydroxycrotonic acid under stirring, raise the temperature to 60°C, then add 98% concentrated sulfuric acid dropwise, complete the addition in 60 minutes, raise the temperature to 80°C, reflux for 6 hours, cool naturally to room temperature, add saturated sodium carbonate solution to the reaction mixture, shake and mix evenly, let stand for 20 minutes, separate the liquid to obtain an organic phase, add saturated brine to the organic phase, shake and wash, then vacuum dry and distill under reduced pressure to obtain a modifier; wherein the mass ratio of the intermediate, 4-hydroxycrotonic acid and concentrated sulfuric acid is 1:2.2:0.03, and the volume ratio of concentrated sulfuric acid, saturated sodium carbonate solution and saturated brine is 1:15:10;
[0046] S3. Dispersing polypropylene fiber and benzoyl peroxide in xylene under stirring and nitrogen atmosphere, raising the temperature to 45°C, reacting for 55 minutes, then raising the temperature to 70°C, continuing the reaction for 40 minutes, removing xylene, adding the modifier obtained in step S2, reacting at 80°C for 80 minutes, naturally cooling to room temperature, washing the reaction product with water and then soaking it with acetone, then extracting it with acetone for 12 hours, and vacuum drying to obtain modified polypropylene fiber; wherein the mass ratio of polypropylene fiber, benzoyl peroxide and modifier is 100:5:18, and the amount of benzoyl peroxide added to xylene is 12 g / L; the grafting rate of the modified polypropylene fiber is determined by acid-base titration, and the grafting rate is 7.7%.
[0047] Example 4
[0048] A cement composite material containing steel slag waste, comprising the following components in parts by weight: 95 parts of cement, 28 parts of modified steel slag, 27 parts of fly ash, 27 parts of mineral powder, and 16 parts of modified polypropylene fiber;
[0049] The preparation method of the modified steel slag is as follows: dispersing the steel slag in an acetic acid aqueous solution with a mass fraction of 5%, introducing carbon dioxide gas (gas purity is 98%), controlling the partial pressure of carbon dioxide to be 0.4 MPa, activating at a temperature of 180° C. for 4 hours, cooling to room temperature, separating the solid from the liquid, taking the solid, drying it, and grinding it into particles with a particle size of less than 0.075 mm to obtain the modified steel slag; wherein the solid-liquid ratio of the steel slag to the acetic acid aqueous solution is 0.35 g / mL;
[0050] The preparation method of the modified polypropylene fiber is:
[0051] S1. After 4-(2-aminoethyl)pyridine and 3-(3-(bromomethyl)phenyl)propionic acid are mixed uniformly, the temperature is increased to 55°C, stirred for 50 min, and then tetrabutylammonium bromide is added, and the temperature is increased to 90°C, refluxed for 7 h under stirring, and naturally cooled to room temperature. Toluene is added to the reaction mixture for extraction, and the mixture is shaken and mixed uniformly. The mixture is allowed to stand for 30 min, and the organic phase is obtained by separation. A 10wt% sodium hydroxide aqueous solution is added to the organic phase, and the mixture is shaken and mixed uniformly. The organic phase is taken after standing for stratification, and then washed with deionized water, vacuum dried, and distilled under reduced pressure to obtain an intermediate; wherein the molar ratio of 4-(2-aminoethyl)pyridine, 3-(3-(bromomethyl)phenyl)propionic acid, and tetrabutylammonium bromide is 1.6:1.35:0.035, the volume ratio of toluene, 10wt% sodium hydroxide aqueous solution, and deionized water is 100:50:60, and the mass volume ratio of 4-(2-aminoethyl)pyridine to toluene is 0.3 g / mL;
[0052] S2. Mix the intermediate obtained in step S1 and 4-hydroxycrotonic acid under stirring, raise the temperature to 65°C, then add 98% concentrated sulfuric acid dropwise, complete the addition in 40 minutes, raise the temperature to 85°C, reflux for 5.5 hours, cool naturally to room temperature, add saturated sodium carbonate solution to the reaction mixture, shake and mix evenly, let stand for 20 minutes, separate to obtain an organic phase, add saturated brine to the organic phase, shake and wash, then vacuum dry and distill under reduced pressure to obtain a modifier; wherein the mass ratio of the intermediate, 4-hydroxycrotonic acid and concentrated sulfuric acid is 1:2.1:0.027, and the volume ratio of concentrated sulfuric acid, saturated sodium carbonate solution and saturated brine is 1:15:10;
[0053] S3. Dispersing polypropylene fiber and benzoyl peroxide in xylene under stirring and nitrogen atmosphere, raising the temperature to 50°C, reacting for 40 minutes, then raising the temperature to 80°C, continuing the reaction for 40 minutes, removing xylene, adding the modifier obtained in step S2, reacting at 90°C for 65 minutes, naturally cooling to room temperature, washing the reaction product with water and then soaking it with acetone, then extracting it with acetone for 12 hours, and vacuum drying to obtain modified polypropylene fiber; wherein the mass ratio of polypropylene fiber, benzoyl peroxide and modifier is 100:4.5:17, and the amount of benzoyl peroxide added to xylene is 11 g / L; the grafting rate of the modified polypropylene fiber is measured by acid-base titration, and the measured grafting rate is 8.3%.
[0054] Comparative Example 1
[0055] A cement composite material containing steel slag waste comprises the following components in parts by weight: 70 parts of cement, 15 parts of modified steel slag prepared in Example 1, 20 parts of fly ash, 20 parts of mineral powder, and 5 parts of modified polypropylene fiber prepared in Example 1.
[0056] Comparative Example 2
[0057] A cement composite material containing steel slag waste comprises the following components in parts by weight: 70 parts of cement, 20 parts of modified steel slag prepared in Example 1, 25 parts of fly ash, 25 parts of mineral powder, and 15 parts of polypropylene fiber.
[0058] The cement composite materials containing steel slag waste described in Examples 2-4 and Comparative Examples 1-2 were prepared according to the method described in Example 1.
[0059] Relevant tests were conducted on the cement composite materials containing steel slag waste prepared in Examples 1-4 and Comparative Examples 1-2. Cement, modified steel slag, fly ash, mineral powder, modified polypropylene fiber, and water were uniformly mixed (the mass ratio of cement to water was 100:150), and mortar was mixed and formed. After standard curing for 24 hours, curing was continued, the curing temperature was 20±1°C, and the curing relative humidity was ≥95%, and a sample was obtained. The 28d compressive strength and 28d flexural strength tests were carried out in accordance with GB / T50081-2019 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", and the mechanical properties of the test specimens before and after aging were tested. The aging conditions were: 72h at 250℃; for the impact resistance test, a round cake-shaped specimen with a diameter of 150mm and a thickness of 65mm was made. The mass of the impact ball was 5kg, the diameter of the impact ball was 65mm, and the height of the impact frame ensured that the distance between the center of mass of the impact ball and the surface of the specimen was 500mm, and the number of final crack impacts was recorded; the penetration resistance, early plastic cracking area, and 28d drying shrinkage tests were carried out in accordance with GB / T50082-2019 "Standard for Test Methods for Physical Long-term Properties and Durability of Ordinary Concrete", and the penetration resistance test was carried out using the water seepage height method; the above tests were repeated three times and the average value was taken. The test results are shown in Table 1. It can be seen from the data in Table 1 that, compared with Comparative Examples 1-2, the cement composite materials containing steel slag waste prepared in Examples 1-4 have lower drying shrinkage, and also have excellent mechanical properties, impact resistance, impermeability and crack resistance. After aging at 250°C for 72h, the cement composite materials containing steel slag waste prepared in Examples 1-4 have a 28d compressive strength of more than 60MPa and a 28d flexural strength of more than 11.5MPa, showing good thermal stability.
[0060] Table 1 Test results of relevant properties of cement composite materials containing steel slag waste
[0061]
[0062] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.
Claims
1. A cement composite material containing steel slag waste, characterized in that: The invention comprises the following components in parts by weight: 80-100 parts of cement, 20-40 parts of modified steel slag, 20-30 parts of fly ash, 20-30 parts of mineral powder, and 10-20 parts of modified polypropylene fiber; The preparation method of the modified polypropylene fiber is as follows: S1. Mix 4-(2-aminoethyl)pyridine and 3-(3-(bromomethyl)phenyl)propionic acid evenly, raise the temperature to 50-60° C., stir for 30-50 min, then add tetrabutylammonium bromide, raise the temperature to 90-100° C., reflux for 5-7 h under stirring, cool to room temperature, and purify to obtain an intermediate; S2. The intermediate obtained in step S1 and 4-hydroxycrotonic acid are uniformly mixed under stirring conditions, the temperature is raised to 60-70° C., concentrated sulfuric acid is then added dropwise over 40-60 min, the temperature is then raised to 80-90° C., the reaction is refluxed for 4-6 h, the mixture is cooled to room temperature, and a modifier is obtained after purification; S3. Disperse polypropylene fiber and benzoyl peroxide in xylene under stirring and nitrogen atmosphere, raise the temperature to 45-55° C., react for 45-55 min, then raise the temperature to 70-90° C., continue to react for 20-40 min, remove the solvent, add the modifier obtained in step S2, react at 80-90° C. for 60-80 min, cool to room temperature, and obtain modified polypropylene fiber after purification.
2. The cement composite material containing steel slag waste according to claim 1, characterized in that: The molar ratio of 4-(2-aminoethyl)pyridine, 3-(3-(bromomethyl)phenyl)propionic acid and tetrabutylammonium bromide in step S1 is 1.6:1.3-1.5:0.03-0.
05.
3. The cement composite material containing steel slag waste according to claim 1, characterized in that: The mass ratio of the intermediate, 4-hydroxycrotonic acid and concentrated sulfuric acid in step S2 is 1:1.8-2.2:0.02-0.
03.
4. The cement composite material containing steel slag waste according to claim 1, characterized in that: The mass ratio of the polypropylene fiber, benzoyl peroxide and modifier in step S3 is 100:3-5:14-18.
5. The cement composite material containing steel slag waste according to claim 4, characterized in that: The amount of benzoyl peroxide added to the xylene is 8-12 g / L.
6. The cement composite material containing steel slag waste according to claim 1, characterized in that: The preparation method of the modified steel slag is as follows: dispersing the steel slag in an acetic acid aqueous solution, introducing carbon dioxide gas, controlling the partial pressure of carbon dioxide to be 0.4 MPa, activating at a temperature of 170-190° C. for 3-5 hours, cooling to room temperature, separating the solid from the liquid, taking the solid, drying and grinding the solid to obtain the modified steel slag.
7. The cement composite material containing steel slag waste according to claim 6, characterized in that: The solid-to-liquid ratio of the steel slag to the acetic acid aqueous solution is 0.3-0.5 g / mL, and the mass fraction of acetic acid in the acetic acid aqueous solution is 2-5%.
8. The cement composite material containing steel slag waste according to claim 6, characterized in that: The particle size of the modified steel slag is less than 0.075 mm.
9. The method for preparing a cement composite material containing steel slag waste according to any one of claims 1 to 8, characterized in that: The cement, modified steel slag, fly ash, mineral powder and modified polypropylene fiber are uniformly mixed to obtain the product.
Citation Information
Patent Citations
Steel slag aggregate lightweight fiber foam concrete
CN104529302A
Cited By
Basalt fiber composite rubber reinforced concrete and preparation method thereof
CN121248241A
Basalt fiber composite rubber reinforced concrete and a preparation method thereof
CN121248241B
High-performance cement composite material containing steel slag and preparation method thereof
CN122426985A